2020
DOI: 10.1007/s42865-020-00011-8
|View full text |Cite
|
Sign up to set email alerts
|

In situ sounding of radiative flux profiles through the Arctic lower troposphere

Abstract: In situ profiles and fixed-altitude time series of all four components of net radiation were obtained at Ny-Ålesund, Svalbard (78.9° N, 11.9° E), in the period May 04–21, 2015. Measurements were performed using adapted high-quality instrumentation classified as “secondary standard” carried by a tethered balloon system. Balloon-lifted measurements of albedo under clear-sky conditions demonstrate the local dependence on altitude and on the surface inhomogeneity of this parameter over coastal terrain of Ny-Ålesun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…5c) shows weak oscillations typically below ± 1 K d −1 centered on the zero line. This case corresponds to the radiative equilibrium where surface and cloud base emit a similar amount of radiation, as previously shown for similar cloud conditions on sea ice (Egerer et al, 2019) and in Ny-Ålesund (Becker et al, 2020). The average profile obtained through low-level water-bearing clouds in summer shows the radiative cooling rates below, in, and above a vertically normalized cloud (Fig.…”
Section: Radiative Cooling Rate Profilessupporting
confidence: 78%
See 2 more Smart Citations
“…5c) shows weak oscillations typically below ± 1 K d −1 centered on the zero line. This case corresponds to the radiative equilibrium where surface and cloud base emit a similar amount of radiation, as previously shown for similar cloud conditions on sea ice (Egerer et al, 2019) and in Ny-Ålesund (Becker et al, 2020). The average profile obtained through low-level water-bearing clouds in summer shows the radiative cooling rates below, in, and above a vertically normalized cloud (Fig.…”
Section: Radiative Cooling Rate Profilessupporting
confidence: 78%
“…While most of the literature discusses the cloud radiative effect at the surface, its height dependence in the atmospheric boundary layer (ABL) is mostly not considered, although it may be significant because of local radiative energy sources and sinks at different altitudes (Curry, 1986;Yamamoto et al, 1995;Asano et al, 2004;Philipona et al, 2020). For example, Turner et al (2018) showed that the vertical structure of irradiance and radiative cooling rate profiles depends on the atmospheric state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1b. The balloon has a volume of about 9 m 3 and allows to lift a modular scientific payload of up to 4 kg (Becker et al, 2020). The setup enables continuously vertical profiling of the lowermost 1.5 km of the atmosphere with a climbing rate of 1 to 2 m s −1 .…”
Section: Observations In the Winter And Spring Seasons During The Mos...mentioning
confidence: 99%
“…An overview of the atmospheric measurements is given by Shupe et al (2022), and information about the sea ice and oceanographic aspects is summarized by Nicolaus et al (2022) and Rabe et al (2022). Figure 1a shows the course of the drift of RV Polarstern in winter and spring when the tethered balloon Miss Piggy (Becker et al, 2020) was deployed from the ice floe close to RV Polarstern.…”
Section: Observations In Winter and Spring During The Mosaic Expeditionmentioning
confidence: 99%